Empowered Educators: How High-Performing Systems Shape Teaching Quality Around the World - Darling-Hammond, Linda; Burns, Dion; Campbell, Carol; Goodwin, A. Lin; Hammerness, Karen; Low, Ee-Ling; McIntyre, Ann; Sato, Mistilina; Zeichner, Ken (Jossey-Bass, 2017)
Discover how high-performing systems shape teaching quality around the world Producing highly skilled and committed teachers is not the work of a single innovative school or the aggregation of heroic individuals who succeed against the odds. In high-performing countries, the opportunities for teachers to learn sophisticated practices and continue to improve are embedded systemically in education policies and practices. Empowered Educators describes how this seemingly magical work is done—how a number of forward-thinking educational systems create a coherent set of policies designed to ensure quality teaching in all communities. . . and how the results are manifested in practice. Spanning three continents and five countries, Empowered Educators examines seven jurisdictions that have worked to develop comprehensive teaching policy systems: Singapore and Finland, the states of New South Wales and Victoria in Australia, the provinces of Alberta and Ontario in Canada, and the province of Shanghai in China. Renowned education expert Linda Darling-Hammond and a team of esteemed scholars offer lessons learned in a number of areas that shape the teaching force and the work of teachers, shedding unprecedented light on areas such as teacher recruitment, preparation, induction and mentoring, professional learning, career and leadership development, and more. Find out how quality teaching is developed and conducted across the globe Discover a common set of strategies for developing, supporting, and sustaining the ongoing learning and development of teachers and school leaders See how high-performing countries successfully recruit and train educators Understand why the sharing of expertise among teachers and administrators within and across schools is beneficial A fascinating read for researchers, policymakers, administrators, teacher educators, pre-service teachers and leaders, and anyone with an interest in education, this book offers a rare glimpse into the systems that are shaping quality teaching around the world.